Lean Thinking in Small Size Assembly Company for Continuous Improvement - Bai, Xue (My University, 2009)
There is a Chinese saying told “Save time means living longer, waste less means owns more.” Lean should always be considered as a philosophy, rather than tools. Simply copy some Lean techniques might get significant results in a short time and the person who applied those techniques became the hero of the factory. However, if Lean philosophy is not properly understood, the dirty and bad organized factory will come back. This thesis is concentrated on applying Lean as a philosophy by tailored techniques to small sized company, especially in assembly lines. Quanti-Quali research method is used to analyze the feasibility of expected results. In theoretical section, different Lean tools and strategies is introduced and studied based on the needs of small companies standpoint. In empirical part, a company based solution is proposed concerning short throughput time, optimized batch sizes, low WIP, zero inventories, just in time, zero quality control and so on. Quantitative data will be analyzed; root problems and bottlenecks will be defined. To get a general view of the company operation process, value stream mapping is used to get a bird’s eye view. With the help of VSM, a future state of operation in such a small company is studied and applied.
Keywords: Lean philosophy; continuous improvement; one-piece flow; zero inventory.; fi=Tuotantotalous|en=Industrial Management|